High resolution spectra of 13C ethane and propane isotopologues photoacoustically measured using interband cascade lasers near 3.33 and 3.38 µm, respectively. (April 2019) - Loh, Alain; Wolff, Marcus
Highlights: High resolution absorption spectra of 12 CH3 - 13 CH3 and 13 CH3 - 13 CH3 around 3.33 µm. High resolution absorption spectra of 12 CH3 - 12 CH2 - 13 CH3 around 3.38 µm. Photoacoustic measurements using cw, TEC, DFB interband cascade lasers. Abstract: We report measurements of short-chained hydrocarbon isotopologues using two continuous wave (cw), thermoelectrically cooled (TEC), distributed feedback interband cascade lasers (DFB-ICLs) around 3.33 and 3.38 µm. The high resolution absorption spectra of 12 CH3 - 13 CH3, 13 CH3 - 13 CH3 and 12 CH3 - 12 CH2 - 13 CH3 were recorded at room temperature and atmospheric pressure for concentrations of approximately 0.1% in nitrogen using photoacoustic spectroscopy (PAS). For calibration and analysis purposes the 13 C spectra as well as ethane and propane spectra at natural abundance are compared to respective FTIR spectra originating from the HITRAN database and results of a previous study. The high resolution absorption spectra will allow isotopologue-sensitive spectral analyses of ethane and propane in this spectral region and may be used as reference data for applications from atmospheric and planetary research to natural gas exploration.